2006
DOI: 10.1385/mb:33:2:141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Effective siRNA Blocking the Expression of SARS Viral Envelope E and RDRP Genes

Abstract: A cell-based assay was developed to screen small interference RNA (siRNA) to block the expression of two genes of the severe acute respiratory syndrome (SARS) virus. These two genes encode RNA-dependent RNA polymerase (RDRP) and envelope E protein. The RDRP plays an essential role in viral RNA replication where envelope E protein is involved in envelope formation and virus assembly. The RDRP and envelope E genes, based on published sequences, have been synthesized and cloned into mammalian expression vectors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…siRNA targeting the E, M and N proteins , leader sequence, TRS, 3 -UTR or the S gene Qin et al, 2004;Zhang et al, 2004) could effectively inhibit the expression of these targets. Plasmid-derived siRNA targeting to RDRP (Meng et al, 2006;Wang et al, 2004), the leader sequence (B.J. T.…”
Section: Introductionmentioning
confidence: 99%
“…siRNA targeting the E, M and N proteins , leader sequence, TRS, 3 -UTR or the S gene Qin et al, 2004;Zhang et al, 2004) could effectively inhibit the expression of these targets. Plasmid-derived siRNA targeting to RDRP (Meng et al, 2006;Wang et al, 2004), the leader sequence (B.J. T.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all anti-SARS siRNA inhibited viral gene expression. This finding suggested a novel approach for the inhibition of production of viral proteins leading to treatment of SARS (Meng et al, 2006;Bitko and Barik, 2007).…”
Section: Preclinical Rdrp Inhibitorsmentioning
confidence: 95%
“…There are two approaches to produce siRNAs in mammalian cells, the first is under the control of specific promoters to form doublestranded siRNA, and the second is through a hairpin structure where siRNAs are expressed as hairpin structures and subsequently processed to siRNA intracellularly. Meng et al employed both the approaches to produce several siRNA molecules to test against SARS-CoV RdRP and envelope E protein (Meng et al, 2006). In this study, a cell-based assay was developed for screening siRNA to inhibit the expression of two genes that encode envelope E protein and RdRP of SARS-CoV.…”
Section: Preclinical Rdrp Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations